Improving Poetry Writing Skills Through Concept Sentence Learning Models in Students - Istoriana, Ayu; Wafda, Andi (Pustaka Digital Indonesia, 2023)
The purpose of this study was to improve poetry writing skills in Indonesian language learning for SD Negeri 03 Jatisari students through the concept sentence learning model. This research involved fifth grade students with a total of 14 students. The research took place in two cycles. Acquisition of value from pre-cycle to cycle I increased by 7.6%. Even though the average score obtained in cycle I did not meet the KKM because it received a score of 74.3, this was already good because it had increased from 66.7 to 74.3. From cycle I to cycle II there was an increase in value of 5.8% with a total value in cycle II of 80.1 and the percentage of completeness was 83.7%, which means it was successful. In cycle II, the average student has met and exceeded the set KKM. The conclusion of this study is that the poetry writing skills of SD Negeri 03 Jatisari students can be improved through the application of the concept sentence learning model. The findings in this study are First, students are not familiar with group work activities because so far students have not worked much in groups. Second, students are not familiar with the Concept Sentence learning model. Third, students are still not very enthusiastic about working with groups because maybe they are not in the same group as the friends they want. Fourth, in terms of reading poetry in front of the class, group representatives still looked shy and also when the teacher asked student representatives to conclude today's lesson, none of the students wanted to and in the end the teacher had to appoint.